Non-Prescription Medicinal Products Exclusively Dispensed in Pharmacies in Portugal - Elisabete Gonçalves; Ana Marcelo; Sérgio Vilão; José Aranda da Silva; Ana Paula Martins (Formifarma, LDA., 2016)
Self-medication is a process through which the individual assumes a greater degree of responsibility for the management of a minor health problem, by acquiring a medicine that is accessible without the need to obtain a medical prescription. Access to health care is undergoing important changes in the European Union. In the presence of factors such as aging populations and economic constraints on health systems, greater emphasis to the efficient use of health resources has been given. Self-care, which comprises self-medication assumes, in this context, an important role by encouraging individuals to take greater responsibility for their own health and wellbeing, choose healthy life choices, consult the pharmacist when appropriate and to establish whether and when medical treatment should be sought. In order to promote the rational use of medicinal products, the subcategory of non-prescription medicinal products exclusively dispensed in pharmacies has gained expression in different European countries. As the name implies, this category includes medicines that, by their nature and given the framework of the condition for which they are intended, are considered safe for dispensing without the requirement of a prescription, possess some attribute that makes them elective for dispensing under the supervision of a health professional, in this case the pharmacist, in order to promote safety and efficiency in their use. The different Member States have advanced at different times with the implementation of this category of classification regarding the dispensing to the public of medicines. Portugal introduced in 2013 this category of medicines in its legal framework. If, on one hand, the big drivers for the classification of more medicines in categories non-prescription medicinal products and non-prescription medicinal products exclusively dispensed in pharmacies have been the greater empowerment of the patient regarding the management of his health and the reduction of expenditure on medicines by health systems, the rational and safe use of medicines has conditioned the progress in this area at European level. The reclassification of a medicine and / or the corresponding indication is associated with several benefits and risks, which affect not only the consumer, also having an impact on health professionals, doctors and pharmacists, insurance companies and institutions / state authorities. The need for the discussion of this issue in our country, with the participation of the different stakeholders involved: the regulatory authority, health professionals, the pharmaceutical industry and patients should be emphasized.